Relationships Between Accounting Professional Intelligence and Audit Quality of Certified Public Accountants in Thailand - Chanlawong, Kuljira; Wangcharoendate, Suwan; Prempanichnukul, Varaporn (Interdisciplinary Academic and Research Journal, 2023)
The advancement of technology has resulted in an economy driven by big data and intelligent software for the accountants is a profession that is facing enormous changes. As a result, auditing standards have changed. Accountants therefore have to adjust and increase capabilities to meet the needs of the changing business world. Thus, this research has the objectives 1) to study the Accounting Profession Intelligence of Certified Public Accountants in Thailand 2) to study the Audit Quality of Certified Public Accountants in Thailand 3) to test the relationship between accounting profession intelligence and audit quality of Certified Public Accountants in Thailand; 4) to test the impact of accounting profession intelligence on audit quality of Certified Public Accountants in Thailand; and 5) to compare accounting profession intelligence and Audit Quality of Certified Public Accountants in Thailand with gender, age, education level auditing experience number of businesses audited each year the number of hours trained in auditing or other related fields and the location is different; The samples number of 144 people. The questionnaire was employed as the research tool and statistics adopted for data analysis were comprised of frequency, percentage, mean, standard deviation, multiple correlation analysis, and multiple regression analysis. The study revealed these results: Certified Public Accountants in Thailand agreed with hanging Accounting Profession Intelligence and audit quality. Overall, each aspect was at a high level. In a comparison of professional accounting intelligence and audit quality of certified public accountants in Thailand classified by gender, age, education level, auditing experience number of businesses audited each year, and the number of hours trained in auditing or other related fields, there were no differences in. opinions about the intelligence of professional accounting and the quality of auditing overall. When considering each aspect, it was found that they were not different. From the correlation and effects analysis, it was found that accounting professional intelligence was positively correlated with the auditing quality of certified public accountants in Thailand; Accounting Professions on Auditing Quality of Certified Public Accountants in Thailand found that Accounting Professional Intelligence affected the Audit Quality of Certified Public Accountants in Thailand. statistically significant at the <.05 level by the result of creative quotient visionary intelligence Experience Intelligence and technical intelligence and ethics, respectively.